2017
DOI: 10.3390/mi9010004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Back Wall Dross and Surface Roughness in Fiber Laser Microcutting of 316L Miniature Tubes

Abstract: Laser cutting is a key technology for the medical devices industry, providing the flexibility, and precision for the processing of sheets, and tubes with high quality features. In this study, extensive experimentation was used to evaluate the effect of fiber laser micro-cutting parameters over average surface roughness (Ra) and back wall dross (Dbw) in AISI 316L stainless steel miniature tubes. A factorial design analysis was carried out to investigate the laser process parameters: pulse frequency, pulse width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Separate experimental designs were applied to each tube diameter, with two replicates for pulse overlapping and pulse energy factors (see Table 4 ), while argon gas assisted the process (P A = 4.1 bar). These process parameters were selected according to a previous experiment with laser cutting of miniature stainless steel tubes, with the same order of magnitude in wall thickness [ 33 ]. Considering that magnesium alloys have a higher thermal conductivity (~3 times) than stainless steel materials, the process parameters were selected in the same range as the cited work.…”
Section: Methodsmentioning
confidence: 99%
“…Separate experimental designs were applied to each tube diameter, with two replicates for pulse overlapping and pulse energy factors (see Table 4 ), while argon gas assisted the process (P A = 4.1 bar). These process parameters were selected according to a previous experiment with laser cutting of miniature stainless steel tubes, with the same order of magnitude in wall thickness [ 33 ]. Considering that magnesium alloys have a higher thermal conductivity (~3 times) than stainless steel materials, the process parameters were selected in the same range as the cited work.…”
Section: Methodsmentioning
confidence: 99%
“…Kathuria et al [48] applied the short pulse Nd-YAG laser to fabricate a stent with a diameter of 2.0 mm and a length of 20 mm and found that the cutting surface quality can be improved by controlling the heat-affected zone and dross removal process. Erika et al [49] investigated the formation mechanism of back wall dross and surface roughness during fiber laser micro-cutting of 316 L miniature tubes and fabricated the stents with a surface roughness of less than 1 µm and dross deposits of less than 3.5%. Bear et al [50] designed and fabricated a novel laser-activated shape memory polymer stent, and the deformation of the fabricated stents was calibrated in a water-filled artery model in vitro.…”
Section: Laser Cuttingmentioning
confidence: 99%
“…Laser cutting [44][45][46][47][48][49][50][51][52][53][54][55][56] Good quality High processing accuracy Heat-affected zone 3D printing [57][58][59][60][61][62][63][64] Personalized customization High material utilization Poor accuracy µEDM…”
Section: Difficult To Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the effect of scanning speed on the microgroove geometry was more critical compared to the laser pulses. García-López et al 6 focused on assessing process parameters' influence on average surface roughness (R a ) and back-wall dross during fiber laser micro-cutting of small SS tubes. The study revealed that the highest level of spot overlaps (60%-93%) reduced average surface roughness by a considerable amount.…”
Section: Introductionmentioning
confidence: 99%